Enhancement of Raman scattering from single-walled carbon nanotubes on densely-arranged two-dimensional gold nanoparticle assemblies. (2nd September 2017) - Inoue, Wataru; Igari, Shuto; Uchida, Koji; Sugawa, Kosuke; Otsuki, Joe
ABSTRACT: We investigated surface-enhanced Raman scattering properties of single-stranded DNA-functionalized single-walled carbon nanotubes (ssDNA-SWCNTs) modified on densely-arranged two-dimensional Au nanoparticle assemblies. The ssDNA-SWCNTs was prepared by sonicating a mixture solution of the ssDNA and high-pressure carbon monoxide (Hipco) SWNTs. The Au nanoparticle assemblies were prepared by an organic solvent-mediated liquid-liquid interface assembly technique. The assemblies showed a strong longitudinal dipole coupling mode, which lead to the generation of hot spots at a near infrared region. The Raman signals characteristic of the SWCNTs were significantly enhanced (average enhancement factor: 199) by the coupling mode.